Gender and crime : contemporary theoretical perspectives - Browning, Sandra Lee; Butler, Leah C.; Jonson, Cheryl Lero (New York, NY : Routledge, 2024)
"This volume takes stock of contemporary perspectives on gender and crime. In 1975, Freda Adler published her pathbreaking book, Sisters in Crime: The Rise of the New Female Criminal. She made the bold claim that changes in American society-including changing attitudes and opportunities-would allow for greater participation of women in criminal enterprises. Beyond her substantive thesis, which turned out to be partially accurate, Adler opened up a vibrant new area within criminology: the study of gender and crime. Now nearly a half century later, the field of criminology is replete with women scholars who are making plentiful and important contributions. As a result, this volume explores cutting-edge issues. Part I starts by laying out a theoretical foundation, focusing on the origins of theories of female criminality and then providing an overview of more contemporary perspectives. Part II explores the role of race in shaping women's criminality, drawing on the novel approaches of "Black Criminology" and the study of intersectionality. Part III gives attention to issues that heretofore were male-centric, illuminating female desistance from crime, the effects of peer groups, and gender differences in attitudes toward criminal justice policies. Finally, Part IV considers the explanation of three important realms of criminality-risky lifestyles, white-collar crime, and terrorism. This volume will be of interest to a wide range of criminologists and is an ideal choice for use in graduate seminars and upper-level undergraduate courses"--
Keywords: Female offenders; Intersectionality (Sociology); Crime; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Gender Studies